(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: Coronavirus disease 2019 (COVID-19) may caused life-threatening situations and provide challenges to medical education,as teachers should lecture safely by the electronic learning. The aim of this study is to evaluate the knowledge, attitudes, and satisfaction ofmedical students in Iraq about E-learning during COVID-19 pandemic. Subject and Material: A cross-sectional study was conducted amongmedical students at 20 universities in Iraq using a Google Form containing a 25-question study -questionnaire that includes socioeconomicand demographic information, also information regarding online medical learning and the status of medical education during COVID-19Knowledge and attitudes related to the epidemic and learning electronic.Results: Most respondents (53.3%) disagreed that E-learning, while16.4% of the respondents agree about that, the others are having neutral attitude. On the other hand, their attitude about electronic examswas positive in which majority of them (54%) agreeing that E-testing can replace others testing methods. Most respondents conduct thatthe best way of E-learning is explanatory downloadable videos (46.7%) followed by online classes with discussion (44.5%). Although Iraqimedical students are facing many difficulties as in poor internet web (major complication; 57.5%), problems in dealing with the technologydevices, poor communication with the teaching staff, insufficient understanding of the scientific material, inappropriate time of lectures andpsychological problems like anxiety, E-learning has a list of advantages among Iraqi medical students such as time saving (53.3%), lesscost, comfortable, ability to ask questions at any time, about 57.8% of students use E-learning more than 4 hours in day after pandemic.Conclusion:most students had not use E-learning before the COVID-19 pandemic, so there is a difference between time spent on E-learningbefore and after this pandemic, There is a relatively negative attitude of Iraqi medical students toward E-learning, also the best way ofE-learning is explanatory downloadable videos , followed by online classes with discussion , as well as the attitude of medical studentsabout electronic exams was positive agreed that E-testing can replacement the others traditional testing methods and E-learning has manyadvantages among Iraqi medical students and Several difficulties in same time.